Συντελεστής αντίστασης διαφόρων γεωμετρικών σχημάτων με εσωτερική ροη - Λάμπρου, Μαρία (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The purpose of this work is the experimental study of the drag coefficient of various geometrical shapes, his relationship with various geometric shapes and how altered when there is internal flow. The experiments were performed in the laboratories of the Department of Mechanical Engineering and Materials Science at Technological University of Cyprus, the building Sikopetritis within the wind tunnel. Ten figures used a solid cylinder and a solid sphere and four cylinders and spheres with a hole of one, two, three and four centimeters along the axis. In the first phase of experiments measured the resistance of the shapes at different speeds. In the second phase, internal flow created in order to study the change of resistance and the rate of deterioration due to this flow. In this paper we refer to all machinery and equipment used during the experiments, their cultures and the methodology that we followed. Also, the various factors that may have affected the measurements and problems encountered during the experimental trials are presented. Then the measurements and the results obtained from the integration of experiments and graphs of resistance in function of the rate of air flow in the wind tunnel are presented as well as the behavior of the drag coefficient in each experimental study and comparisons between shapes.
Keywords: Drag Coefficient; Geometrical Shapes; Speed; Ιnternal Flow; Συντελεστής Αντίστασης; Γεωμετρικά Σχήματα; Ταχύτητα; Εσωτερική Ροή